2023
DOI: 10.1038/s41598-023-37125-w
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength rather than appendicular skeletal muscle mass might affect spinal sagittal alignment, low back pain, and health-related quality of life

Abstract: Sarcopenia is defined as decreasing in muscle strength and mass, and dynapenia is defined as decreasing in muscle strength and maintained muscle mass. This study elucidated the prevalence and characteristics of sarcopenia and dynapenia and evaluate in elderly spinal disorders patients. 1039 spinal disorders patients aged ≥ 65 years were included. We measured age, grip strength, muscle mass, spinal sagittal alignment parameters, low back pain (LBP) scores and health-related quality of life (HR-QoL) scores. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This does not fit into the general frame of our study design, because patients with SCI participating in this study were, in general, young adults, with a mean age of 41 years in the NS-SCI group and 35 years in the S-SCI group; this reinforces the above mentioned hypothesis, and aligns with epidemiological studies regarding the average age at which SCIs occur, which was 37.6 years in a study from 2000 [45]. Another study published in 2023 by Tanaka et al (N = 1039) found a statistically significantly higher mean age in the sarcopenic group compared with the non-sarcopenic one [46]. However, secondary sarcopenia occurs if other factors, besides aging, are evident in the study sample, as per our research [47].…”
Section: Discussionsupporting
confidence: 84%
“…This does not fit into the general frame of our study design, because patients with SCI participating in this study were, in general, young adults, with a mean age of 41 years in the NS-SCI group and 35 years in the S-SCI group; this reinforces the above mentioned hypothesis, and aligns with epidemiological studies regarding the average age at which SCIs occur, which was 37.6 years in a study from 2000 [45]. Another study published in 2023 by Tanaka et al (N = 1039) found a statistically significantly higher mean age in the sarcopenic group compared with the non-sarcopenic one [46]. However, secondary sarcopenia occurs if other factors, besides aging, are evident in the study sample, as per our research [47].…”
Section: Discussionsupporting
confidence: 84%